First, you set up your equation then you put the pieces together to get the answer
Answer:
Y = (x + 3)(x - 4)(x + 1)^2
Y = (x^2 - x - 12)(x^2 + 2x + 1)
Y = x^4 + 2x^3 + x^2 - x^3 - 2x^2 - x - 12x^2 - 24x - 12
Y = x^4 + x^3 - 13x^2 - 25x - 12
I'm pretty sure you already solved this by now, but I'll say the answer anyway. This problem has already been solved by another as a verified answer.
This is the concept of financial algebra, we are required to calculate the value of stock ABC which follows the model given by:
y=12.21x+37.42
given that x=62 days,
the value of th estock after 62 days will be given by:
y=12.21(62)+37.42
y=757.02+37.42
y=794.44
ABC will be worth $794.44
I take no credit for this answer. It was solved by CastleRook.
Answer:
25x^2 -1
Step-by-step explanation:
If you multiply parentheses:
(5x*5x) + (5x*-1) + (1*5x) + (1*-1)
25x^2 - 5x + 5x -1
25x^2 -1
A simpler way is to memorize this formula
(Square1 - square2)= (sqrt of square1- sqrt of square2)*(sqrt of square1 + sqrt of sqaure2)
Answer:
2x²y³
<em>good luck, i hope this helps :)</em>